KESALAHAN FONOLOGI, MORFOLOGI, SINTAKSIS PADA FILM “AYAH, INI ARAHNYA KE MANA, YA?” KARYA KUNTZ AGUS - Ridho Sastro Panjaitan; Tabita Tesalonika Simaremare; Mutiara Aprilia; Mannawa Salwa; Muharinna Harahap (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to explore language errors in phonology, morphology, and syntax in the film "Ayah, Ini Arahnya ke Mana, Ya?" (Father, This is the Direction to Where, Ya?), written by Kuntz Agus. Film, as a form of mass communication, functions not only as a means of recreation but also as a representation of everyday language use. Language error analysis was conducted to identify various forms of deviations that occur in the characters' dialogues. This study uses a descriptive qualitative method, using listening and recording techniques to identify utterances containing errors in phonology, morphology, and syntax. Phonological errors include changes, omissions, or additions of sounds that do not comply with Indonesian language rules. Morphological errors include the use of affixes, word formation, and inappropriate word choice. Meanwhile, syntactic errors include inaccuracies in constructing phrases, clauses, and sentences, which impact the effectiveness of communication. The findings of this study are expected to provide a general overview of language use in Indonesian films and serve as a reference for learning correct and effective Indonesian. In addition, this study can also broaden insights into language error analysis in audiovisual media, a field of applied linguistics.